Shift [large type] : managing your emotions--so they don't manage you - Kross, Ethan (Random House Large Print, 2025)
"Whether it's anxiety about going to the doctor, boiling rage when we're stuck in traffic, or devastation after a painful break-up, our lives are filled with situations that send us spiraling. But as difficult as our emotions can be, they are also a superpower. Far from being "good" or "bad," emotions are information. When they're activated in the right ways and at the right time, they function like an immune system, alerting us to our surroundings, telling us how to react to a situation, and helping us make the right choices. But how do we make our emotions work for us rather than against us? Acclaimed psychologist Dr. Ethan Kross has devoted his scientific career to answering this question. In Shift, he dispels common myths--for instance, that avoidance is always toxic or that we should always strive to live in the moment--and provides a new framework for shifting our emotions so they don't take over our lives. Shift weaves groundbreaking research with riveting stories of people struggling and succeeding to manage their emotions--from a mother whose fear prompted her to make a spur-of-the-moment decision that would save her daughter's life mid-flight to a nuclear code-carrying Navy SEAL who learned how to embrace both joy and pain during a hellish training activity. Dr. Kross spotlights a wide array of tools that we already have access to--in our bodies and minds, our relationships with other people, and the cultures and physical spaces we inhabit--and shows us how to harness them to be healthier and more successful. Filled with actionable advice, cutting-edge research, and riveting stories, Shift puts the power back into our hands, so we can control our emotions without them controlling us--and help others do the same."